Reproductive biology of Chamaeleo pumilus pumilus (Microsauria pumilus) with special reference to the role of the corpus luteum and progesterone - Veith, Walter Julius (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1973.